Usability and performance expectancy govern spine surgeons’ use of a clinical decision support system for shared decision-making on the choice of treatment of common lumbar degenerative disorders - Eiskjær, Søren; Pedersen, Casper Friis; Skov, Simon Toftgaard; Andersen, Mikkel Østerheden (Frontiers in Digital Health, 2023)
Study design: Quantitative survey study. Objectives: The aim of the current study was to develop a model for the factors that drive or impede the use of an AI clinical decision support system (CDSS) PROPOSE supporting the shared decision making on the choice of treatment of ordinary spinal disorders. Methods: Sixty-two spine surgeons were asked to answer a questionnaire regarding behavioral intention to use the CDSS after being presented for PROPOSE. The model behind the questionnaire was the unified theory of acceptance and use of technology (UTAUT). Data were analyzed using PLS-SEM. Results: The most important and significant factors were the degree of ease of use associated with the new technology -effort expectancy/usability followed by performance expectancy -the degree to which an individual believes that using a new technology will help him or her to attain gains in job performance. Social influence and trust in the CDSS were other factors in the path model. r 2 for the model was 0.63 -indicating that almost two thirds of the variance in the model was explained. The only significant effect in the multigroup analyses of path differences between two subgroups was for PROPOSE use and social influence (p = 0.01) Conclusion: Shared decision making is essential to meet patient expectations in spine surgery. A trustworthy CDSS with ease of use and satisfactory predictive ability and promoted by the leadership will stand the best chance of acceptation and bridging the communication gap between surgeon and patient.